IMPLEMENTING A STUDENT PORTFOLIO IN A GRAMMAR CLASS USING COMMUNICATIVE APPROACH - Rukminingsih, Rukminingsih; Novianti, Hartia (JEELL (Journal of English Education, Linguistics and Literature) English Department of STKIP PGRI Jombang, 2015)
Model-based learning portfolio is a learning model that has a strong basicprinciples such as the principle of active learning, cooperative learning groups, learningpartisipatorik and reactive. Besides, it has a strong thought that Re-education andreflection on the learning experience (Wayatt Looper, s1999: 31). This research has beenconducted to determine the effectiveness of the learning model with grammar basedstudent portfolio. The study design was quasi-experimental with pretest-posttest group ofnon-random. In collecting the data, two sets of grammar tests used for the pretest and theother is for the posttest, and questionnaires. Hypothesis testing used ANCOVA test. Theresults of the data analysis showed that 1) the application of the learning model portfolioget better achievement Grammar than students who learn grammar in a conventionalway, 2) The results of the questionnaire showed that overall student response to themodel portfolio of learning grammar with very positively.